Criteria heterogeneity in the diagnosis of acute bronchiolitis in Spain - Alfredo Cano-Garcinuño; Manuel Praena-Crespo; Isabel Mora-Gandarillas; Ignacio Carvajal-Urueña; María Teresa Callén-Blecua; Águeda García-Merino; Cristina Calvo; Ángeles Cansino-Campuzano; José Carlos Flores-González; Mirella Gaboli; María Luz García-García; Luis García-Marcos; et al. (Elsevier, 2019)
Introduction: Acute viral bronchiolitis (AB) is one of the most common respiratory diseases in infants. However, diagnostic criteria for AB are heterogeneous and not very well known. Objective: To identify the diagnostic criteria for AB used by experts and clinical paediatricians in Spain. Methods: Delphi study with Spanish AB experts, looking for the points of agreement about AB diagnosis. A subsequent cross-sectional study was conducted by means of an online questionnaire addressed to all Spanish paediatricians, reached through electronic mail messages sent by nine paediatric scientific societies. Descriptive and factorial analyses were carried out, looking for any association of diagnostic criteria with demographic or geographic variables, or with paediatric subspecialty. Results: Agreement was reached by 40 experts in many issues (first episode of respiratory distress and high respiratory frequency, diagnosis in any season of the year, and usefulness of virus identification in making diagnosis), but opposite views were maintained on key characteristics such as the maximum age for diagnosis. The online questionnaire was completed by 1297 paediatricians. Their diagnostic criteria were heterogeneous and strongly associated with their paediatric sub-specialty. Their agreement with the Spanish expert consensus and with international standards was very poor. Conclusions: Diagnostic criteria for AB in Spain are heterogeneous. These differences could cause variability in clinical practice with AB patients. Resumen: Introducción: La bronquiolitis vírica aguda (BA) es una de las enfermedades respiratorias más frecuentes en los lactantes. Sin embargo, los criterios utilizados para su diagnóstico son heterogéneos e insuficientemente conocidos. Objetivo: Identificar los criterios de diagnóstico de BA empleados en España, tanto por expertos como por pediatras clínicos. Métodos: Estudio de metodología Delphi con expertos españoles en BA, buscando los puntos de consenso sobre el diagnóstico de BA. Posteriormente se realizó un estudio transversal mediante encuesta online dirigida a todos los pediatras españoles, contactados a través de mensajes de correo electrónico enviados por nueve sociedades científicas pediátricas. Se hizo análisis descriptivo y análisis factorial de los resultados de la encuesta, buscando si los criterios diagnósticos empleados se relacionaban con variables demográficas, geográficas o con la subespecialidad pediátrica. Resultados: Los 40 expertos participantes alcanzaron un consenso en muchos aspectos (primer episodio de dificultad respiratoria y aumento de la frecuencia respiratoria, diagnóstico en cualquier estación del año, y utilidad de la identificación de virus para el diagnóstico), pero manteniendo opiniones enfrentadas en cuestiones importantes como la edad máxima aceptable para el diagnóstico. A la encuesta online respondieron 1297 pediatras. Los criterios diagnósticos que aplican son heterogéneos y están fuertemente asociados con la subespecialidad pediátrica. Su acuerdo con el consenso de expertos y con estándares internacionales es muy bajo. Conclusiones: Los criterios usados en España para el diagnóstico de BA son heterogéneos. Esas diferencias pueden causar variabilidad en la práctica clínica en pacientes con BA.